MANAGEMENT OF NITROGEN STRESS IN COTTON (Gossypium hirsutum L.) USING GREENSEEKER TECHNOLOGY - Medine KARATAS; Emine KARADEMIR (Journal of Applied Life Sciences and Environment)
This study was performed with GreenSeeker technology in order to determine the possibility of nitrogen stress management in cotton and to determine the differences between the normalized difference vegetative index (NDVI) and nitrogen doses determined with GreenSeeker, to determine the nitrogen deficiency and stress conditions by making use of the value of the NDVI in cotton production and to intervene when necessary and direct the producers in this regard. In the study six nitrogen doses (Control, 60, 120, 180, 240 and 300 kg ha-1) were used. The results showed significant differences between N applications for leaf chlorophyll content (SPAD), NDVI-2 (in the boll formation period), number of bolls (NB), seed cotton (SCY) and fiber yield (FY). On the other hand, there were non-significant differences in terms of (LA) area, NDVI-1 (in the beginning of the flowering), plant height (PH), node number of first fruiting branches (NNFFB), number of monopodial branches (NMB) and number of sympodial branches (NSB), number of nodes (NN), height to node ratio (HNR), seed cotton boll weight (SCBW) and ginning percentage (GP). The highest SCY and FY obtained were from doses of 180 and 120 kg ha-1 N, the highest leaf chlorophyll content and number of bolls obtained were from doses of 120 kg ha-1 N. The highest values of NDVI-2 obtained were from doses of 120, 240 and 300 kg ha-1 N, respectively. There were non-significant differences between N doses for values of the NDVI-1 of flowering, but significant differences observed for values of NDVI-2 of boll formation periods. The findings obtained from this research indicated that leaf chlorophyll and NDVI of the boll formation period can be used for determining differences due to varying N doses in cotton production.